Antifungal activity of bioactive compound of seeds of Psoralea corylifolia L. against seed borne Fusarium species of maize - Kiran. B, Lalitha.V, Raveesha.K.A (Journal of Applied Pharmaceutical Science)
Antifungal activity of bioactive compound 2H-Furo[2,3-H]-1-benzopyran-2-one isolated from seeds of Psoralea corylifolia L. were tested against eight Fusarium species of maize seeds at 100- 1000ppm concentration. F. moniliforme, F. oxysporum, F. semitectum and F. solani were completely inhibited at 600ppm concentration. F. equiseti, F. lateritium and F. proliferatum were completely inhibited at 700ppm concentration and F. graminearum was inhibited at 800 ppm concentration. Significant inhibition was also observed from 100-500ppm concentration in all the test fungi. Compared to synthetic fungicide Thiram recorded significant antimicrobial activity than Captan tested at 2000ppm concentration. Minimum Inhibitory Concentration (MIC) was also determined for all the species of Fusarium tested. In dry mycelia weight analysis, the mycelia growth all the species of Fusarium were completely inhibited at 500-650 ppm concentration of the bioactive compound.
Keywords: 2H-Furo[2,3-H]-1-benzopyran-2-one, Psoralea corylifolia, Fusarium, Thiram, Captan.